(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This study aims to overcome some authors‘ feeling that ―everyday life‖ is a vague, problematic and polysemous concept which, for those reasons, is unreachable and even imperceptible. This task is more relevant at present, considering the central importance that ―everyday life‖ category has gained in contemporary studies. We have approached this task starting from the analysis of different problems: first, the question of the universality of this concept; second, its narrative nature, its heterogeneity and necessary homogeneity (regulations); third, the possible motivations; fourth, its interruption or break down; then, its difference and proximity to the concept of ―routine‖ and; finally, its consequences: dis-enchantment and boredom.